Green Human Resource Management and Organizational‎Citizenship Behavior: The Influence of Eco-FriendlyLifestyle and Organizational Commitment - Aiswarya, U Bala; Manivel , Kalaivani (International Journal of Accounting and Economics Studies, 2025)
In response to growing global concerns about environmental sustainability, both governments and ‎corporations have increasingly prioritized eco-conscious initiatives, prompting multinational ‎companies to embed sustainable practices within their strategic frameworks. This study explores the ‎connection between Green Human Resource Management (GHRM) and employees’ Organizational ‎Citizenship Behavior for the Environment (OCBE), with a particular focus on the mediating role of ‎green lifestyle and the moderating role of organizational commitment. Data were collected from 407 ‎working professionals across four key sectors—information technology, manufacturing, banking, and ‎healthcare—applying the Attitude–Behavior–Context (ABC) framework alongside Social Exchange ‎Theory. Structural Equation Modeling (SEM) was performed using AMOS to analyze the ‎relationships. The findings reveal that GHRM has a significant positive effect on OCBE. ‎Furthermore, while a green lifestyle serves as a partial mediator in this relationship, organizational ‎commitment was found to moderate the strength of this effect. The results provide actionable ‎insights for practitioners, suggesting that integrating environmental principles into HR practices can ‎promote voluntary eco-friendly behavior among employees and reinforce broader corporate ‎sustainability efforts‎.
Keywords: Eco-Friendly Lifestyle; Green Human Resource Management; Organizational Citizenship Behavior ‎for the Environment; Organizational Commitment; Workplace Sustainability‎.